Particle migration in oscillatory torsional flows of concentrated suspensions - Deshpande, Kapil V.; Shapley, Nina C. (Journal of rheology (New York : 1978), 2010)
This study presents an experimental investigation into particle migration behavior of concentrated suspensions of noncolloidal spheres in oscillatory torsional flows between parallel plates. Video imaging of the radial drift velocity of dyed tracer particles in a monodisperse, 0.4 bulk particle volume fraction suspension was performed during flow evolution. In conjunction with simultaneous rheological measurements, particle tracking provided insight into migration phenomena. For all of the cases studied, the average displacement of the tracer particles per cycle was directed radially outward and was approximately a linear function of the oscillatory strain amplitude while also varying with the frequency of oscillation in a nearly inverse square relationship. The measured radial migration velocity exceeded that estimated from the suspension balance continuum model for a corresponding steady flow, likely due to the increased microstructural mobility developed during oscillatory flow. Generally, the oscillatory torque increased as the flow evolved, while local minima in the torque ratio and radial drift velocity were detected at intermediate strain values, in agreement with recent studies of oscillatory flow. The results suggest the competition between radial shear-induced particle migration driven by the overall particle stress balance and rearrangement of particles into an ordered microstructure driven by local interactions.